THE IMPACT OF ARTIFICIAL INTELLIGENCE: PROGRESS OR REGRESSION? - Ro‘zimboyeva Shaxina Otabekovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial Intelligence (AI) has become one of the most transformative forces in modern society. This article delves into both the benefits and the drawbacks of AI integration into key sectors such as healthcare, economy, public life, culture and especially education. The discussion analyzes how AI has improved efficiency, decision-making, and accessibility while also examining the accompanying risks, including job displacement, ethical dilemmas, irresponsibility, partially plagiarism, and data privacy concerns. Through a balanced approach, the article aims to highlight the dual nature of AI — as a driver of progress and as a source of new social challenges. Ultimately, the goal is to evaluate whether AI represents a net improvement or a potential threat to human well-being and the growth of their mindset.